2019
DOI: 10.1002/cbic.201900505
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of APOBEC3 DNA‐Mutator Isozymes by Fluoro‐ and Non‐Fluoro‐Substituted 2′‐Deoxyzebularine Embedded in Single‐Stranded DNA

Abstract: The APOBEC3 (APOBEC3A‐H) enzyme family is part of the human innate immune system that restricts pathogens by scrambling pathogenic single‐stranded (ss) DNA by deamination of cytosines to produce uracil residues. However, APOBEC3‐mediated mutagenesis of viral and cancer DNA promotes its evolution, thus enabling disease progression and the development of drug resistance. Therefore, APOBEC3 inhibition offers a new strategy to complement existing antiviral and anticancer therapies by making such therapies effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 65 publications
(66 reference statements)
5
52
1
Order By: Relevance
“…Based on the position of the SEC elution profile, we conclude that peak 1 corresponds to homo-dimeric A3B CTD * (with a molecular weight of ~44 kDa, referred to as ‘A3B CTD * dimer’). This contrasts with the other A3B CTD variants we reported in previous studies [ 59 , 61 , 80 ], A3B CTD -QM-ΔL3, A3B CTD -QM-ΔL3-E255A, and A3B CTD -DM, which eluted only as monomeric species. Previous reports have suggested that A3A exists as both a monomer and a dimer in vitro [ 52 , 53 ].…”
Section: Resultscontrasting
confidence: 99%
“…Based on the position of the SEC elution profile, we conclude that peak 1 corresponds to homo-dimeric A3B CTD * (with a molecular weight of ~44 kDa, referred to as ‘A3B CTD * dimer’). This contrasts with the other A3B CTD variants we reported in previous studies [ 59 , 61 , 80 ], A3B CTD -QM-ΔL3, A3B CTD -QM-ΔL3-E255A, and A3B CTD -DM, which eluted only as monomeric species. Previous reports have suggested that A3A exists as both a monomer and a dimer in vitro [ 52 , 53 ].…”
Section: Resultscontrasting
confidence: 99%
“…Further exploration is necessary to find efficient and specific Ades in addition to those tested in this study. In addition to virus-derived Ades, it has been reported that single-stranded binding proteins, small-molecule inhibitors and chemically modified oligonucleotides can suppress the cytosine deaminase activity of APOBEC deaminases 60 65 . These potential antagonists of deaminases merit further exploration to develop new inhibitors of CBEs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As APOBEC3B has been shown to be associated with mutations in genomic DNA, tumorigenesis, and drug resistance, it is a potential therapeutic target for cancer treatment. Inhibiting APOBEC3B via modified single-stranded DNA and thereby reducing the risk of genomic mutations ( 43 45 ) and targeting uracil DNA glycosylases to selectively inhibit tumor cells with high APOBEC3B expression ( 46 ) have been described as possible strategies. However, it is unclear whether the former can reduce the frequency of TP53 mutations in DLBCL and the latter can prevent R/R in DLBCL.…”
Section: Discussionmentioning
confidence: 99%